Developing the field of Work Integrated Learning (WIL) in higher education: a scoping study and curriculum inquiry - Rosse, Stephanie (My University, 2014)
The goal of the research is to develop a unified description of the Work Integrated Learning (WIL) Curriculum and a cross-disciplinary curricular framework that identifies the elements and the relationships between them. This research combined scoping study and curriculum inquiry methods and featured three cycles of data analysis and two types of curriculum theorization. Data sources included a literature review, a survey, expert interviews, and a focus group. In theorizing the WIL Curriculum in higher education, the authors develop a definition of the WIL curriculum and on the basis of this definition, put forward a unified curricular framework, as recommended by Cooper, Orrell and Bowden (2010). It begins with a WIL schema to provide an underlying organizational structure that outlines the relationships between fundamental actors and factors in the WIL Curriculum and describes twelve shared dimensions of WIL which are defined in relationship to their function in WIL curriculum development. We also propose a template for curriculum development in WIL and CSL. Finally, based on the data analysis and on patterns found to occur in cross-disciplinary data, we developed eight WIL curriculum models: Awareness, Application, Competency, Synthesis, Deconstruct-Reconstruct, Iterative Reflection, Research-Based, and Problem-Based Models. The WIL models that are advanced in this research provide a starting place for further inquiry, curriculum development and research.
Developing the field of Work Integrated Learning (WIL) in higher education: a scoping study and curriculum inquiry
Presented June 2-4, 2014 at WACE 10th International Symposium on Cooperative & Work-Integrated Education held at University West, Trollhattan, Sweden.
Keywords: Work Integrated Learning; curriculum development